The LMO2 -25 Region Harbours GATA2-Dependent Myeloid Enhancer and RUNX-Dependent T-Lymphoid Repressor Activity. - Nicolas Bonadies; Berthold Göttgens; Fernando J Calero-Nieto (PLoS ONE)
Lim domain only 2 (LMO2) is a transcriptional co-factor required for angiogenesis and the specification of haematopoietic cells during development. LMO2 is widely expressed within haematopoiesis with the exception of T-cells. Failure to downregulate LMO2 during T-cell maturation leads to leukaemia, thus underlining the critical nature of context-dependent regulation of LMO2 expression. We previously identified a distal regulatory element of LMO2 (element -25) that cooperates with the proximal promoter in directing haematopoietic expression. Here we dissected the functional activity of element -25 and showed it to consist of two modules that conferred independent and cell-type specific activities: a 3' myeloid enhancer and a 5' T-cell repressor. The myeloid enhancer was bound by GATA2 in progenitors and its activity depended on a highly conserved GATA motif, whereas the T-cell repressor moiety of element -25 was bound by the Core Binding Factor in T-cells and its repressive activity depended on a highly conserved RUNT motif. Since the myeloid enhancer and nearby downstream region is recurrently involved in oncogenic translocations, our data suggest that the -25 enhancer region provides an open chromatin environment prone to translocations, which in turn cause aberrant LMO2 expression in T-cells due to the removal of the adjacent T-cell repressor.